2020
DOI: 10.1073/pnas.2010056117
|View full text |Cite
|
Sign up to set email alerts
|

Using dynamic monitoring of choices to predict and understand risk preferences

Abstract: Navigating conflict is integral to decision-making, serving a central role both in the subjective experience of choice as well as contemporary theories of how we choose. However, the lack of a sensitive, accessible, and interpretable metric of conflict has led researchers to focus on choice itself rather than how individuals arrive at that choice. Using mouse-tracking—continuously sampling computer mouse location as participants decide—we demonstrate the theoretical and practical uses of dynamic assessments of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 75 publications
1
27
0
Order By: Relevance
“…rhesus macaques vs. capuchins, see Beran et al, 2016 ; or bonobos vs. chimpanzees, see Heilbronner, Rosati, Stevens, Hare, & Hauser, 2008 ). There is some evidence consistent with this in humans, for example, a recent computer mouse-tracking study with human participants demonstrated a close relationship between tracking metrics that were comparable to the operationalization of wavering used in our study and subjective risk perception as well as individual risk aversion ( Stillman, Krajbich, & Ferguson, 2020 ). Alternatively, risk-averse individuals or species may differ more strongly with regard to how sensitive they are in noticing their self-generated cues, or in learning to respond to them with second-order behavior.…”
Section: Discussionsupporting
confidence: 85%
“…rhesus macaques vs. capuchins, see Beran et al, 2016 ; or bonobos vs. chimpanzees, see Heilbronner, Rosati, Stevens, Hare, & Hauser, 2008 ). There is some evidence consistent with this in humans, for example, a recent computer mouse-tracking study with human participants demonstrated a close relationship between tracking metrics that were comparable to the operationalization of wavering used in our study and subjective risk perception as well as individual risk aversion ( Stillman, Krajbich, & Ferguson, 2020 ). Alternatively, risk-averse individuals or species may differ more strongly with regard to how sensitive they are in noticing their self-generated cues, or in learning to respond to them with second-order behavior.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, it has recently been shown that decision-makers change how they interact with their options as they become more and more familiar with them, as evidenced by changes in their gaze patterns (S. E. Cavanagh, Malalasekera, Miranda, Hunt, & Kennerley, 2019). Finer-grained estimates of choice dynamics such as gaze or mouse tracking therefore hold promises for further elucidating interactions between strategic/heuristic processes and more comprehensive evaluations (Callaway, Rangel, et al, 2021;Hunt et al, 2016;Jang et al, 2021;Stillman, Krajbich, & Ferguson, 2020). Computational models that explicitly address these interactions may then also scale better to larger choice sets, where strategies that reduce information processing costs play a much more prominent role (Thomas et al, 2021), and could provide insights into the mechanisms by which decision-making is adapted to changing contextual demands (Teoh et al, 2020).…”
Section: Decisions and Control Over Future Research Directionsmentioning
confidence: 99%
“…and recorded mouse cursor trajectories as participants clicked a button labeled 'yes' or 'no'. We expected all participants to click 'yes,' but for trajectories to veer closer to 'no' among participants with a goal to defend, indicating greater difficulty in providing the correct response (Stillman, Krajbich, & Ferguson, 2020;Melnikoff, Mann, Stillman, Shen, & Ferguson, 2021).…”
Section: Pilot Studymentioning
confidence: 99%